2015
DOI: 10.1093/infdis/jiv320
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Epidemics of Community-Associated Methicillin-ResistantStaphylococcus aureusUSA300 Infection in North and South America

Abstract: Our results reveal the existence of 2 parallel USA300 epidemics that shared a recent common ancestor. The simultaneous rapid dissemination of these 2 epidemic clades suggests the presence of shared, potentially convergent adaptations that enhance fitness and ability to spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
181
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(206 citation statements)
references
References 46 publications
21
181
3
1
Order By: Relevance
“…The isolates recovered in Suriname carried the ACME element characteristic for the USA300-NA clade28. The isolates analyzed in this study also showed fluoroquinolone-resistance with the same mutations in grlA (S80Y) and gyrA (S84L) (Table 2) like those found in the USA300-NA clade, which has spread globally10.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The isolates recovered in Suriname carried the ACME element characteristic for the USA300-NA clade28. The isolates analyzed in this study also showed fluoroquinolone-resistance with the same mutations in grlA (S80Y) and gyrA (S84L) (Table 2) like those found in the USA300-NA clade, which has spread globally10.…”
Section: Discussionsupporting
confidence: 53%
“…Recent phylogenetic analyses28 revealed 2 dominant clades within the USA300 lineage that had a putative common ancestor in 1975 but segregated by geographical region, in North America (USA300 North American, USA300-NA) and in South America (USA300 Latin American variant, USA300-LV). The isolates recovered in Suriname carried the ACME element characteristic for the USA300-NA clade28.…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin‐resistant Staphylococcus aureus (MRSA) is widely distributed throughout the world, including mainland Ecuador (Planet et al, ). Originally, healthcare‐associated MRSA infections have emerged in the community and also from livestock in recent years (Stefani et al, ), becoming epidemic and causing severe disease and often fatal outcomes in humans (DeLeo & Chambers, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic variants were mapped on the trees and correlated with phenotypic changes. For example, Planet and coworkers 39 worked on USA300 and USA300-LV clones, while Stinear and colleagues 40 on CA-MRSA ST93. Stegger et al 41 studied CC80 and Baines et al 42 focused their efforts on HA-MRSA ST239.…”
Section: Global Trends the Explosion Of Salmonella Typhi H58mentioning
confidence: 99%